PENGARUH PERAN SISTEM ELEKTRONIK E-FILLING TERHADAP WAJIB PAJAK DALAM PELAPORAN SPT TAHUNAN TERHADAP KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING ( STUDI EMPIRIS SEMARANG TIMUR) (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2019)
Efforts to collect taxes for the benefit of national development are still experiencing problems both from internal and external factors. In overcoming obstacles from internal factors, the Government has currently and is conducting tax reforms at the Directorate General of Taxes with the aim of, among others, improving the organization, work processes, data and information management from banks, and human resources. the level of compliance with the provisions of tax regulations in reporting taxpayers compliance in reporting Annual Tax Returns to the East Semarang KPP in 2018 is better and increased than in 2016 before meeting the expected target of the East Semarang Pratama Tax Office even though there are still taxpayers reporting in manually expected Taxpayers to report the annual tax return electronicallyWith the Website Application, the role of the E-Filling system on Taxpayers can obtain convenience and input and at the same time help the Community of SPT Reports become faster and more efficient.